2022
DOI: 10.32674/jcihe.v14i3a.4168
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Scholarly Productivity, Supports, and Challenges of Multinational, Female Graduate Students During a Global Pandemic

Abstract: The onset of the COVID-19 pandemic led to shifts in higher education globally. This study reports the tensions multinational women graduate students experienced due to the change in delivery methods caused by the pandemic. Additionally, they examined how the students felt about their changing roles and lived experiences. This study highlights areas that institutions should address along with the type and level of support provided to their graduate student population. The authors recommend that institutions foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…For example, one member opted to wait to engage in COVID GAP during the second phase of research while another found herself unable to participate in the team at all due to COVID-19. This left three members of this subgroup who have one article proposal that was submitted and accepted for consideration in a special issue and the article (Chance et al, 2021) is currently under review and two team members have also collaborated on a book chapter proposal.…”
Section: Outcomes Of Phase One Datamentioning
confidence: 99%
“…For example, one member opted to wait to engage in COVID GAP during the second phase of research while another found herself unable to participate in the team at all due to COVID-19. This left three members of this subgroup who have one article proposal that was submitted and accepted for consideration in a special issue and the article (Chance et al, 2021) is currently under review and two team members have also collaborated on a book chapter proposal.…”
Section: Outcomes Of Phase One Datamentioning
confidence: 99%